1998
DOI: 10.1089/thy.1998.8.1157
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Inhibits Aromatase Activity in Porcine Thecal Cells Cultured Alone and in Coculture with Granulosa Cells

Abstract: We cultured porcine thecal and granulosa cells alone or in coculture to define whether thyroid hormone affects aromatase activity in porcine ovarian cells. Dispersed cells were cultured with 10(-9) M triiodothyronine (T3) for 24 hours. Testosterone (final concentration 10(-7) M) was added as aromatase substrate for granulosa cells (Gc) cultured alone. Thecal (Th) androgens serve as a substrate for estradiol secretion by Th cells cultured alone and in coculture with Gc. At the end of the preincubation time, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In an in vitro system, T 3 caused about a twofold increase of protein synthesis in rat granulosa cells compared to cells without T 3 (Bandyopadhyay et al, 1996). In vitro T 3 assisted FSH and LH to enhance steroid biosynthesis in porcine (Chan and Tan, 1986;Maruo et al, 1987;Gregoraszczuk et al, 1998) and human (Goldman et al, 1993;Wakim et al, 1995a, b) granulosa cells. A recent study has reported that T 3 mediated stimulation of P 4 release from human luteal cells is not direct, but is mediated through a putative protein factor (Datta et al, 1998).…”
Section: Yroid Hormonal Regulation Of Ovarian Endocrine Functionmentioning
confidence: 99%
“…In an in vitro system, T 3 caused about a twofold increase of protein synthesis in rat granulosa cells compared to cells without T 3 (Bandyopadhyay et al, 1996). In vitro T 3 assisted FSH and LH to enhance steroid biosynthesis in porcine (Chan and Tan, 1986;Maruo et al, 1987;Gregoraszczuk et al, 1998) and human (Goldman et al, 1993;Wakim et al, 1995a, b) granulosa cells. A recent study has reported that T 3 mediated stimulation of P 4 release from human luteal cells is not direct, but is mediated through a putative protein factor (Datta et al, 1998).…”
Section: Yroid Hormonal Regulation Of Ovarian Endocrine Functionmentioning
confidence: 99%
“…In porcine GCs, T 4 stimulates FSH-induced estradiol and progesterone secretion (26). Wakim et al (25) additionally demonstrated that T 4 augments steroidogenesis in human GCs.…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, these hormones significantly inhibit apoptosis during in vitro cultivation of porcine granular layer cells. They also participate in the regulation of steroidogenesis by inducing or inhibiting the effect on steroidogenic enzymes [39] [40].…”
Section: Factors Influencing Follicular Steroidogenesismentioning
confidence: 99%